1979
DOI: 10.1111/j.1476-5381.1979.tb07883.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Calcium in the Super‐sensitivityproduced by Cocaine in Cat Spleen Strips

Abstract: Cocaine (2 × 10−6m and 10−5m) produced 2 and 7 fold shifts to the left of the dose‐response curve to (—)‐noradrenaline recorded isotonically in isolated splenic capsular strips of the cat. The same concentrations of cocaine also produced increases in the maximum response of the tissue to 117% and 126.7% of control. Desmethylimipramine (DMI, 10 −7 to 10−6m) produced no significant potentiation of the response of cat spleen strips to (—)‐noradrenaline. At 10−5 M DMI decreased the maximum response. Cocaine (10−5m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In rats concurrently given nitrendipine, heart rate increased only by 40%, no tachyarrhythmias or convulsions were seen, and the LDso increased to 618 mg/kg. In isolated cat spleen strips, potentiation of norepinephrine effects by cocaine was reversed by calcium channel antagonists (Summers and Tillman 1979). The authors hypothesized that one action of cocaine is increased calcium flux across cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In rats concurrently given nitrendipine, heart rate increased only by 40%, no tachyarrhythmias or convulsions were seen, and the LDso increased to 618 mg/kg. In isolated cat spleen strips, potentiation of norepinephrine effects by cocaine was reversed by calcium channel antagonists (Summers and Tillman 1979). The authors hypothesized that one action of cocaine is increased calcium flux across cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…First is the direct vasoconstrictive effect mediated via increased influx of calcium across the vascular endothelium as has been proven in animal studies. 8 The other is vasospasm and poor blood flow in the mucosal vessels due to the sympathomimetic effects of cocaine in the gut vasculature. Apart from vasoconstriction, cocaine can cause ischemia by promoting intramural thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine has been reported to potentiate the maximal response in several organs, such as rat vas deferens (2,5) and cat spleen (3,4,17). Many investigations have indi cated that cocaine has not only an inhibitory action on catecholamine uptake mechanism, but also a stimulating action on smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Summers and Tillman (17) observed that in cat spleen, cocaine potentiation was diminished in the presence of SKF525A, a potent calcium influx inhibitor, although the sources of Ca' to be utilized for contraction in this organ were controversial. Their finding suggested that Ca-influx induced by smooth muscle stimulants increased in the presence rather than in the absence of cocaine.…”
Section: Discussionmentioning
confidence: 99%